If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(8 + -6x) = 5x + -26 (8 * 4 + -6x * 4) = 5x + -26 (32 + -24x) = 5x + -26 Reorder the terms: 32 + -24x = -26 + 5x Solving 32 + -24x = -26 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 32 + -24x + -5x = -26 + 5x + -5x Combine like terms: -24x + -5x = -29x 32 + -29x = -26 + 5x + -5x Combine like terms: 5x + -5x = 0 32 + -29x = -26 + 0 32 + -29x = -26 Add '-32' to each side of the equation. 32 + -32 + -29x = -26 + -32 Combine like terms: 32 + -32 = 0 0 + -29x = -26 + -32 -29x = -26 + -32 Combine like terms: -26 + -32 = -58 -29x = -58 Divide each side by '-29'. x = 2 Simplifying x = 2
| 5x^2+75x+270=0 | | x+8=-16+4x | | 32+6x=8(x+3) | | 2(5x-25)=10(x-5) | | 6+3x=-3x-6 | | -7x^2-64+112=0 | | -9+5x=3x+9 | | 2(7v+7)=28+7v | | 7-7x=2x+7 | | 11x^2-37x=0 | | 2(1-2n)=2n+8 | | -9+2x=4x-17 | | 18x^2+3x-10=0 | | -4x^2-4x+168=0 | | 3-x=8(1-6x)-5 | | 7m^2-35m=0 | | 6x^2+42x+60=0 | | 9m^2-54m=0 | | 6x+9=199-5x | | 8+4r=8(-7r+1) | | 6(1+2k)=-k+19 | | X-2(x-3)=-6-5x | | 2-m(5+mx)=3m^2(1-mx) | | 7(-4m+2)=34-8m | | 4x-9=3+4x | | a*b*c=154 | | abc=154 | | .5(3x+2)-.2(x+6)=5 | | 3x^2+21+36=0 | | 8(2j-6)2(4j-4)= | | 8+4x=12x-4 | | 3x-7=x+11 |